False‐Positive Axillary Lymph Nodes Due to Silicone Adenitis on 18F‐FDG PET/CT in an Oncological Setting. Issue 6 (June 2016) - D'hulst, Ludovic; Nicolaij, Daniël; Beels, Laurence; Gheysens, Olivier; Alaerts, Herwig; Van de Wiele, Christophe; Maes, Alex
Abstract : ABSTRACT : The case of a 49‐year‐old transgender individual with a history of bilateral silicone breast implants and a right lung mass proven by biopsy to be a non–small cell lung cancer is presented. In addition to the primary malignancy, a positron emission tomography/computed tomography scan showed contralateral hypermetabolic adenopathy in the left axilla that was suggestive of nodal metastatic disease. Additional imaging and histological examination of the lymph nodes indicated silicone breast implant leakage and silicone adenitis as the underlying cause of the hypermetabolic axillary lymph node.